2013
DOI: 10.1093/jrr/rrt025
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary analysis of risk factors for late rectal toxicity after helical tomotherapy for prostate cancer

Abstract: The purpose of this study is to examine risk factors for late rectal toxicity for localized prostate cancer patients treated with helical tomotherapy (HT). The patient cohort of this retrospective study was composed of 241 patients treated with HT and followed up regularly. Toxicity levels were scored according to the Radiation Therapy Oncology Group grading scale. The clinical and dosimetric potential factors increasing the risk of late rectal toxicity, such as age, diabetes, anticoagulants, prior abdominal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
(24 reference statements)
2
13
0
Order By: Relevance
“…The extra dose to the bladder due to an inappropriate IMRT planning is also of concern. Radiation oncologists usually pay more attention to the DVH of the rectum rather than of the bladder because the definite dose constraint of the bladder is unclear, whereas the recommended dose constraint of the rectum has been reported 32,33 . Several studies have reported conflicting results for the significance of IMRT in managing adverse effects of SRT 23,34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…The extra dose to the bladder due to an inappropriate IMRT planning is also of concern. Radiation oncologists usually pay more attention to the DVH of the rectum rather than of the bladder because the definite dose constraint of the bladder is unclear, whereas the recommended dose constraint of the rectum has been reported 32,33 . Several studies have reported conflicting results for the significance of IMRT in managing adverse effects of SRT 23,34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…reported on IMRT with helical tomotherapy for prostate cancer. They found that the maximum rectal doses, V70, and V60 of the RTOG toxicity ≥ Grade 2 group were significantly higher than those of the ≤ Grade 1 toxicity group according to univariate analysis, while V40 and V20 had no significant relationship with late rectal toxicity [ 13 ]. Thus, the trend for the risk of late rectal toxicity to be correlated with the percentage of the rectum receiving high doses such as V70 or V60 at other institutions was in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reporting genitourinary toxicity after RT have, by and large, been limited by relatively short‐term follow‐up (<5 years) . These short‐term studies show that severe urinary adverse events (UAEs), defined as Radiation Therapy Oncology Group (RTOG) grades 3, 4 or 5, are rare . Unfortunately RT injury accumulates over time and severe complications can arise many years later .…”
Section: Introductionmentioning
confidence: 99%